GAMBARAN TINGKAT PENGETAHUAN KADER KESEHATAN TENTANG DESA SIAGA DI WILAYAH KERJA PUSKESMAS KECAMATAN SALEM KABUPATEN BREBES TAHUN 2013 - Maya Anjarsari; Feti Kumala Dewi (Viva Medika, 2013)
Background: District of Salem is a village that has a lot of idle rural villagenevertheless siaganya yet stable. Standby village management carried out bymembers of the public especially the cadres, who are concerned about healthproblems dikecamatan salem.Objective: To determine the knowledge level overview about the village healthvolunteers on standby at Puskesmas Salem District of Brebes in 2013 by level ofeducation, resources and age.Methods: This research is a quantitative descriptive method with cross sectionalstudy approach. With a sampling technique accidental sampling sample size is 66people. The study used primary data in the form of questionnaires, processeddenagn way of editing, scoring, tabulating.Results: The knowledge level of alert village health volunteers have enoughknowledge that 32 (48.5%). Education and health cadres SMA / MA / equivalentlevel of education is quite a number of 18 people (27.3%). Source of informationcomes from health care workers have a level of knowledge sufficient number of 28(42.4%). Respondents aged 20-35 years have the level of knowledge about anumber of 27 people (40.9%).Conclusion: The majority of health workers have enough knowledge level,educational level SMA / MA / equivalent, received information from the printmedia, aged 20-35 years.Keywords: Knowledge, health cadres, village standby